Pitfalls in Piezoresistivity Testing - Chung, D. D. L. (Journal of electronic materials, 2022)
The field of piezoresistivity (the effect of strain/stress on the electrical resistivity of a material) has been growing exponentially since 1990, with the growth being particularly sharp since 2015, due to the rise of the multifunctionality and smartness of materials and structures. Most research involves composites with low-conductivity matrices (particularly polymers and cement) and high-conductivity fillers (metals and carbons, particularly microfillers and nanofillers). The composites also include high-performance structural materials containing continuous fibers (e.g., carbon fibers). The piezoresistivity enables structural self-sensing (without device incorporation). Unfortunately, pitfalls are common, due to the subject’s interdisciplinary character and the dominance of researchers without adequate background in electrical testing. This commentary coherently describes the common pitfalls, which pertain to the experimental methods of piezoresistivity testing. The specific pitfalls include (i) using two electrodes rather than four electrodes for the resistance measurement, (ii) poor electrode design, (iii) improper electrode placement, (iv) improper design of the piezoresistive material, (v) improper data interpretation, (vi) unreliable determination of the gage factor (fractional change in resistance per unit strain), and (vii) unreliable measurement of the strain. Some of the pitfalls, such as allowing the silver paint to dry before electrode application, cannot be discerned from publications, but are revealed upon private discussion between this author and the authors of those publications (not referenced here to avoid embarrassment to those authors). These pitfalls result in questionable experimental results, which render the associated modeling work insufficiently meaningful. The hope is to improve the quality of future research in this field.